(untitled) (Archive of Conferences, 2021)
In recent years, our scientists have made significant progress in the study of medieval history and spiritual culture of the peoples of Central Asia. However, to date, little has been done to study the late Middle Ages, characterized by a further deepening of feudal relations and the strengthening of the economic and political independence of large land feudal lords, feudal fragmentation and weakening of the state apparatus. However, until now, all the centuries of late feudalism in Central Asia have been studied unevenly and not systematically.